Genetic Rescue of the Dinaric Lynx Population: Insights for Conservation From Genetic Monitoring and Individual‐Based Modelling - Elena Pazhenkova; Matej Bartol; Barbara Boljte; Urša Fležar; Andrea Gazzola; Tomislav Gomerčić; Marjeta Konec; Ivan Kos; Miha Krofel; Jakub Kubala; Ladislav Paule; Mihai Pop; et al. (Evolutionary Applications)
ABSTRACT Inbreeding depression poses a severe threat to small populations, leading to the fixation of deleterious mutations and decreased survival probability. While the establishment of natural gene flow between populations is an ideal long‐term solution, its practical implementation is often challenging. Reinforcement of populations by translocating individuals from larger populations is a viable strategy for reducing inbreeding, increasing genetic diversity and potentially saving populations from extinction. The Dinaric population of Eurasian lynx (Lynx lynx) has faced high inbreeding levels, with effective inbreeding reaching 0.316 in 2019, endangering the population's survival. To counteract this, population reinforcement was implemented between 2019 and 2023, involving the translocation of 12 individuals from the Carpathian Mountains to the Dinaric Mountains of Slovenia and Croatia. We conducted comprehensive genetic monitoring in this area, gathering 588 non‐invasive and tissue samples, which were used for individual identification and estimation of population genetic parameters. We used stochastic modelling to assess the long‐term viability of the Dinaric lynx population post‐translocation and formulate effective conservation strategies. The model predicts that, despite significant improvement of genetic diversity after translocations, inbreeding will return to critical levels within 45 years. Our results highlight the fact that reinforcement is just the first step and that long‐term genetic management is needed to keep the population from sliding back towards extinction. The Dinaric lynx population serves as a compelling example of genetic rescue. The lessons learnt here will be essential for ensuring the viability of the Dinaric lynx in the future and also provide a useful template for conservation of other populations and species facing similar threats.